EFFECTIVENESS OF SOCIAL MEDIA AS A MARKETING AND PROMOTIONAL TOOL FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMEs) CASE STUDY: PT GLOBAL ATCO SUKSESTAMA - Atikah Putriyani; Tri Mulyaningsih (RADJA PUBLIKA, 2026)
This study aims to analyze the effectiveness of using social media as a marketing and promotional tool for micro, small, and medium enterprises (MSMEs), with a case study of PT Global Atco Suksestama. The rapid development of digital technology requires MSMEs to adapt to changes in consumer behavior, which is increasingly reliant on social media for seeking information and conducting transactions. The research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation studies. The findings indicate that the use of social media platforms such as Instagram, Facebook, and TikTok significantly increases promotional reach and brand awareness. However, its effectiveness remains limited by constraints in human resources for content management and by digital marketing strategies that have not yet been optimized. This study concludes that social media is an effective promotional medium for MSMEs when supported by consistent content strategies, accurate audience analysis, and the utilization of digital advertising features.